Validity ICT and CLIA of SARS-CoV-2 Antibody - Fili Oei; Asvin Nurulita; Darwati Muhadi; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
The varying validity of antibody test requires a good diagnostic accuracy analysis in determining the right tome to perform antibody testing in patients. This study is to evaluate sensitivity and specificity of SARS-CoV2 antibody test based on the testing time. This stugy is a cross sectional retrospective diagnostic test study include 960 subject divided into 3 groups based on the testing time using 2 antibody test methods are ICT and CLIA. The sensitivity and specificity of ICT method was 45.8% and 59.7%, while the CLIA method was 81.6% and 74.4%. Based on timing of antibody test after symptom onset, the highest sensitivity was obtained at >15 days of symptom onset (84.4% and 78.7%). Low sensitivity can be caused due to the absence or low antibodies in the first week to second weeks of infection. Sample collection is done 2-4 weeks after symptom onset. The SARS CoV-2 IgM and IgG antibodies have high sensitivity and specificity at onset >15 days (84.4% and 78.7%).